1996
DOI: 10.1097/00007435-199605000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Development of Serum Antibodies to HPV16 and HPV33 and Acquisition of Cervical HPV DNA Among Sexually Experienced and Virginal Young Girls

Abstract: Both HPV serology and HPV DNA testing indicated that the number of sexual partners and earliness of coitus debut determined the risk for acquiring HPV infection and that nonsexually transmitted infections are rare or nonexistent among adolescent girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
2
3

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 23 publications
3
41
2
3
Order By: Relevance
“…Some of the previous studies found considerable variation in the association between HPV 16 exposure and the risk of ESCC when they changed their cutpoints. 9,10 For example, in Bjorge's study 9 the OR for the association of HPV 16 and ESCC changed from 10 for a cutpoint of 0.239 (a level that that had given optimal discrimination of cases and controls in a previous study 27 ) to 2.3 for a cutpoint of 0.100 (a level that distinguishes HPV 16 infected women from sexually inexperienced women 28 ). To overcome this problem, we examined graphs of risk versus type-specific log OD produced by cubic spline logistic regressions and defined a spline cutpoint as the inflection point beyond which the graph either monotonically increased or decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the previous studies found considerable variation in the association between HPV 16 exposure and the risk of ESCC when they changed their cutpoints. 9,10 For example, in Bjorge's study 9 the OR for the association of HPV 16 and ESCC changed from 10 for a cutpoint of 0.239 (a level that that had given optimal discrimination of cases and controls in a previous study 27 ) to 2.3 for a cutpoint of 0.100 (a level that distinguishes HPV 16 infected women from sexually inexperienced women 28 ). To overcome this problem, we examined graphs of risk versus type-specific log OD produced by cubic spline logistic regressions and defined a spline cutpoint as the inflection point beyond which the graph either monotonically increased or decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Discrepancies were resolved by multiple repeat analyses. A panel of serum samples from virginal women was analysed in parallel and no HPV antibodies could be found (Andersson-Ellström et al, 1996).…”
Section: Hpv Serologymentioning
confidence: 99%
“…Serum samples from HPV infected women were selected from 3 previously described population-based epidemiological studies of HPV infection, [8][9][10] where the cohorts were still followed. To maximize the probability of obtaining sera reactive with only 1 HPV genotype, sera were selected where sample donors had indicated that they had had only 1 lifetime sexual partner, although 1 donor who had reported 2-3 partners was also included.…”
Section: Study Samplesmentioning
confidence: 99%